Penerapan Fenomena Bullying pada Tingkat Sekolah Dasar dan Menengah di Desa Banjar Seminai Tahun 2024 - Nizmi, Yusnarida Eka; Hanif, Dhestra Amanullah; Anjelli, Risfa; Pratama, Muhammad Rehan; Firdaus, Muhammad Rifqi; Jumaida, Cut; Rizkhi, Miftahul; Sari, Elen Retno; Athaillah, Dea; Khairunnisa, Khairunnisa; Ridwan, M. (Unri Conference Series: Community Engagement, 2024)
This article explains an issue about bullying that become one of the major obstacles in creating quality, safe, far-from-violence, and inclusive education as emphasized by the United Nations in achieving point 4 of the SDGs. Bullying behavior not only has a significant impact on psychological conditions but also affects the overall learning process for students. Various actions have been implied to overcome bullying in schools, such as implementing an anti-bullying outreach program that has been carried out. Having information that, achieving quality education is also hampered by the lack of detailed data on the prevalence and impact of bullying in schools. To broadly support the achievement of the SDGs, our team of Merdeka Belajar Kampus Merdeka (MBKM) Faculty of Social and Political Sciences, conducted anti-bullying socialization program, exploring the prevalence and dynamics of bullying, especially in schools in Banjar Seminai Village, Dayun District, Siak Regency, which is the location of MBKM from Faculty of Social dan Political Sciences, Universitas Riau. The data was collected by doing socialization and filling out questionnaires after carrying out anti-bullying socialization to students in grades 4, 5, and 6 at SD 03 and 04 Banjar Seminai as well as students and students in grades 7, 8, and 9 at Junior High School (SMP 05 Dayun). This article shows that bullying at Primary School and Junior High School ( SDN 03 and 04 ; SMP 05) Dayun is quiete massive which is priority on verbal bullying.